MULTI-LEVEL GOVERNANCE ANALYSIS IN THE BOUNDARY DISPUTE BETWEEN PALEMBANG CITY AND BANYUASIN REGENCY IN THE TEGAL BINANGUN AREA - Mardianto, Mardianto; Marpaung, Zailani Surya; Junaidi, Junaidi; Khairunnas, Khairunnas (Journal of Social Politics and Governance (JSPG), 2025)
This study examines the dynamics of resolving the regional boundary dispute between Palembang City and Banyuasin Regency in Tegal Binangun within a multi-level governance framework. The trigger for the conflict was Minister of Home Affairs Regulation No. 134/2022, which changed administrative boundaries, eliciting objections from the Palembang City Government and public rejection. A qualitative method using purposive sampling involved informants from the Provincial Government Bureau, the City/Regency Governance Section, and village officials. The data were analyzed using NVivo 15 and supplemented with a literature review. The results indicate that the South Sumatra Provincial Government plays a strategic role as a mediator, while the district/city governments act as policy implementers. However, interactions between levels are not optimal, particularly in terms of communication and coordination at the village level. Community participation remains asymmetrical, and the role of NGOs has not been structurally facilitated, adding to the complexity of the conflict. Minister of Home Affairs Regulation 134/2022 serves as the legal basis for policy integration, but its effectiveness depends on social legitimacy, implementation flexibility, and support from public service information systems. The research recommends cross-actor collaboration, adaptive public communication, and capacity building for local governments to achieve sustainable, fair, and service-oriented dispute resolution.